Respuesta :
Answer:
[tex]y = \frac{3 + 6\sqrt{2} }{4}[/tex] and [tex]y = \frac{3 - 6\sqrt{2} }{4}[/tex]
y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction
Step-by-step explanation:
The given quadratic equation is (4y - 3)² = 72
We have to solve this equation for y.
Now, 4y - 3 = ± 6√2
⇒ 4y = 3 ± 6√2
⇒ [tex]y = \frac{3 + 6\sqrt{2} }{4}[/tex] and [tex]y = \frac{3 - 6\sqrt{2} }{4}[/tex]
Therefore, the solution is y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction (Answer)